Using Text-Based Interactive Games as a Tool for Studying Decision Making Patterns - Tony Tan; Tony Wibowo; Riyaldi Walvinson (Department of Informatics Engineering, Universitas Muhammadiyah Purwokerto, 2026)
Decision making is a key factor in student success and wellbeing. Yet little is known about how interactive games foster reflection on daily habits. This study examined the influence of the text-based game A Day at Home on university students’ free-time activities, satisfaction, and intentions to change habits. A qualitative descriptive design was applied with 29 participants aged 18–25 who completed pre- and post-game questionnaires. Data were analyzed thematically and supported by descriptive statistics. The findings show that most students (52 %) reported consistency between their real-life and in-game free-time activities, while 35 % noted differences. Satisfaction with free-time use remained unchanged for 65.5 % of students but decreased for 34.5 %, indicating greater self-awareness and critical evaluation of current routines. Nearly half (48.3 %) expressed new or stronger intentions to adopt healthier behaviors, such as exercising more or reducing gaming. These results suggest that although the game did not alter habits for the majority, it provided a reflective tool that encouraged students to assess their routines and consider alternatives. The study concludes that text-based interactive games offer a promising approach to support reflection, motivate behavioral change, and enhance student wellbeing in higher education.